Respiration kinetics and allometric scaling in the demosponge Halichondria panicea - Lars Kumala; Malte Thomsen; Donald E. Canfield (BMC Ecology and Evolution, 2023)
Abstract Background The aquiferous system in sponges represents one of the simplest circulatory systems used by animals for the internal uptake and distribution of oxygen and metabolic substrates. Its modular organization enables sponges to metabolically scale with size differently than animals with an internal circulatory system. In this case, metabolic rate is typically limited by surface to volume constraints to maintain an efficient supply of oxygen and food. Here, we consider the linkeage between oxygen concentration, the respiration rates of sponges and sponge size. Results We explored respiration kinetics for individuals of the demosponge Halichondria panicea with varying numbers of aquiferous modules (n modules  = 1–102). From this work we establish relationships between the sponge size, module number, maximum respiration rate (R max ) and the half-saturation constant, K m , which is the oxygen concentration producing half of the maximum respiration rate, R max . We found that the n modules in H. panicea scales consistently with sponge volume (V sp ) and that R max increased with sponge size with a proportionality > 1. Conversly, we found a lack of correlation between K m and sponge body size suggesting that oxygen concentration does not control the size of sponges. Conclusions The present study reveals that the addition of aquiferous modules (with a mean volume of 1.59 ± 0.22 mL) enables H. panicea in particular, and likely demosponges in general, to grow far beyond constraints limiting the size of their component modules and independent of ambient oxygen levels.